Determinants of active aging affect healthy life expectation - theresa, Ria Maria Theresa; dewiastuti, Marlina; Kristanti, Melly; cantika (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Life expectancy is an indicator of successful health development. It is estimated the elderly population will increase along with the increase in life expectancy, in 2050 there will be an increase 3 times in the number of elderly from 2013. The increase in the number of elderly raises a health sector complicated problem. The elderly group will experience a decrease in health status either naturally or due to illness. Goals of the health program focus on life expectancy. West Java is the largest proportion with Indramayu a city in West Java that has a target life expectancy that reaches the target. The government's efforts to improve the elderly welfare are realized in various programs so that an increase in the elderly population does not increase health problems. Indicators of elderly health can be measured by active aging (AA).. The determinants of the AA component, which include health and well-being, are indicators for assessing healthy life expectancy in the elderly. Assessment of healthy life expectancy is assessed from several determinants. Assessment of healthy life expectancy can determine health development targets, especially in the elderly. This study associated dietary patterns and smoking habits with increased healthy life expectancy.